FLORIANÓPOLIS THREE GENERATIONS' TOYS AND GAMES (Fiep Bulletin - online, 2014)
Playing games and playing with toys are important childhood contents of different cultures and generations, full of various meanings and interpretations, depending on the point of view of who is studying these activities. The present study aims to identify which were the games and toys most accepted by children from three different generations, 20 years apart from each other, constituted by teachers, employees, students and senior citizens from the Centro de Desportos of Universidade Federal de Santa Catarina (CDS/UFSC), Florianópolis. For this research, the authors chose to apply a semi-structured questionnaire composed by 36 alternative items and three dissertative answers. The 60 year-old plus generation basically used to play in dynamic activities instead of moderate or sedentary ones, preferring marbles, same as the 40 year-old plus generation - although catch and hide-and-seek were also considerably important in their childhood. In the 20 year-old plus generation, dynamic activities loose space to the moderate and sedentary ones, with special remarks to skateboarding, videogames and action figures. By the means of the marked items by each generation, it's possible to conclude that the games and toys option variability is basically similar from generation to generation: 13,06 items were marked by the 60 year-old plus group; 11,73 items by the 40 plus; and 14,34 by the 20 year-old plus interviewees.
Keywords: games; playing; generations